2018
DOI: 10.1016/j.agsy.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Yield gap analysis and entry points for improving productivity on large oil palm plantations and smallholder farms in Ghana

Abstract: Oil palm production must increase in Ghana to meet the increasing demand for palm oil and avoid costly imports. Although maximum fruit bunch (FB) yields of > 20 t ha −1 yr −1 are achievable, average FB yields in Ghana are only 7 t ha −1 yr −1. Despite the pressing need to increase palm oil production and improve yields, knowledge of the underlying causes of poor yields in Ghana is lacking. Closing yield gaps in existing plantings in smallholdings and plantations offers great opportunities to increase oil produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
5
17
0
1
Order By: Relevance
“…The productivity of oil palm plantations is highly dependent on the supply of resources (e.g., water, fertilizers and sunlight) and on good plantation management practices [ 7 ]. Poor management practices, including incomplete crop recovery (i.e., harvesting all suitable crops) and inadequate agronomic management have been reported as the main factors contributing to FFB yield gaps [ 15 ]. Oil palm productivity can be increased through best management practices (improvement of technical culture) and the use of high-quality seeds (some can produce around 35 tons of FFB/ha) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The productivity of oil palm plantations is highly dependent on the supply of resources (e.g., water, fertilizers and sunlight) and on good plantation management practices [ 7 ]. Poor management practices, including incomplete crop recovery (i.e., harvesting all suitable crops) and inadequate agronomic management have been reported as the main factors contributing to FFB yield gaps [ 15 ]. Oil palm productivity can be increased through best management practices (improvement of technical culture) and the use of high-quality seeds (some can produce around 35 tons of FFB/ha) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low FFB yields is not unique to smallholder farmers in Cameroon. In Ghana, Rhebergen et al [ 15 ] reported that smallholder FFB yields average 7 t/ha/yr.…”
Section: Introductionmentioning
confidence: 99%
“…In international agricultural policy, discussions about oil palm and livelihoods usually focus on the need to increase yield for smallholders (Rhebergen et al, 2018). Our research complicates this framing.…”
Section: Discussionmentioning
confidence: 91%
“…There are no reliable studies which show convincingly that weeding practices have a significant impact on oil palm yield (Woittiez et al, 2017b). An indirect but important benefit of good weeding (especially the establishment of paths and circles) and pruning is that these practices facilitate quick and complete harvesting, which had major impact on yield in a smallholder GAP project in Ghana (IPNI, 2015;Rhebergen et al, 2018). At least one farmer stated that the harvesting costs per tonne in the well-weeded and well-pruned BMP plots were less, because harvesters adapt the price to the effort required for harvesting.…”
Section: Discussionmentioning
confidence: 99%